2016
DOI: 10.1002/ijc.30452
|View full text |Cite
|
Sign up to set email alerts
|

Country‐specific HPV‐related genital disease among men residing in Brazil, Mexico and The United States: The HIM study

Abstract: The purpose of this study was to assess whether the incidence of histopathologically confirmed condyloma and penile intraepithelial neoplasia (PeIN) and rates of genital HPV infection progression to these lesions differs by country (Brazil, Mexico, and the U.S.). At each visit, lesions were biopsied and were categorized by pathologic diagnoses. The Linear Array genotyping method was used to identify HPV genotypes from genital swabs, while the INNO-LiPA HPV Genotyping Extra method was used for tissue specimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Differences in the genital HPV natural history by country may explain the differences in HPV-related disease outcomes that we and other have observed (11, 26). Within the HIM Study , the incidence of genital warts was similar across the three countries, but the incidence of penile intraepithelial neoplasia (PeIN) was higher in Brazil than Mexico and the US, although not statistically significant (26).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Differences in the genital HPV natural history by country may explain the differences in HPV-related disease outcomes that we and other have observed (11, 26). Within the HIM Study , the incidence of genital warts was similar across the three countries, but the incidence of penile intraepithelial neoplasia (PeIN) was higher in Brazil than Mexico and the US, although not statistically significant (26).…”
Section: Discussionmentioning
confidence: 64%
“…Within the HIM Study , the incidence of genital warts was similar across the three countries, but the incidence of penile intraepithelial neoplasia (PeIN) was higher in Brazil than Mexico and the US, although not statistically significant (26). In this study, we observed Brazil to have the highest prevalence and duration of HPV16 infections, which likely explains the higher rate of infection progression to disease (PeIN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men who tested positive for HPV at baseline had nearly 12 times the risk of developing GWs [15], with highest incidence among men aged 18–30 years [67, 69, 72]. GW incidence in Brazil and the United States decreased with age, while the incidence remained constant across the lifespan in Mexico [71]. Among HIM Study participants, 16 and 22% of genital HPV 6 and 11 infections developed into HPV 6 and 11 positive GW respectively [20].…”
Section: Hpv Genital Infection and Associated Diseases: The Him Studymentioning
confidence: 99%
“…HPV-16 infections had a relatively slow rate of progression with 50% of PeIN taking more than 19 months to be detected [20]. There were no differences by country and age for PeIN incidence [71, 72]. …”
Section: Hpv Genital Infection and Associated Diseases: The Him Studymentioning
confidence: 99%